2009
DOI: 10.2527/jas.2009-1853
|View full text |Cite
|
Sign up to set email alerts
|

Growing rate of gain on subsequent feedlot performance, meat, and carcass quality of beef steers1

Abstract: A.; Maddock, R. J.; Stamm, M. M.; Schauer, C. S.; Rush, Ivan G.; Quinn, S.; and Lardy, G. P., "Growing rate of gain on subsequent feedlot performance, meat, and carcass quality of beef steers" (2009 LG diet consisted of 52.5% barley silage, 39.0% whole shell corn, and 8.5% supplement, whereas the HG diet contained 43.9% barley silage, 47.4% whole shell corn, and 8.7% supplement (DM basis). Initial BW (226 kg) was not different (P = 0.70) between treatments. Steers fed the HG diet had increased ADG (1.67 vs. 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The shear force value was not affected by the energy or protein levels or sex with a mean value of 3.14 kg, so can be classified as “very tender” meat. One study has found that the shear force value of meat was 3.62 kg when Angus steers were slaughtered at a younger age of 14 mon with a 14 d post-mortem [38], this value was higher than that found in the present study. A younger slaughter age and longer post-mortem ageing time could produce more tender meat [39,40].…”
Section: Discussioncontrasting
confidence: 84%
“…The shear force value was not affected by the energy or protein levels or sex with a mean value of 3.14 kg, so can be classified as “very tender” meat. One study has found that the shear force value of meat was 3.62 kg when Angus steers were slaughtered at a younger age of 14 mon with a 14 d post-mortem [38], this value was higher than that found in the present study. A younger slaughter age and longer post-mortem ageing time could produce more tender meat [39,40].…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast, Hancock et al (3) reported lower fat thickness, YG, and MARB among low ADG performing animals during the grazing period when fed to a constant weight end point. Loken et al (6) fed two drylot energy rations to create two ADG levels, and concluded that the backgrounding ADG of 1.4 kg/day (low) or 1.7 kg/day (high) did not affect feedlot ADG, and that carcass traits were not affected by these pre‐feedlot ADG. The pasture ADG grouping used in our study represented a wider range of stocker gain during backgrounding.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…3). (6) fed two drylot energy rations to create two ADG levels, and concluded that the backgrounding ADG of 1.4 kg/day (low) or 1.7 kg/day (high) did not affect feedlot ADG, and that carcass traits were not affected by these pre-feedlot ADG. The pasture ADG grouping used in our study represented a wider range of stocker gain during backgrounding.…”
Section: Feedlot Performancementioning
confidence: 99%
See 1 more Smart Citation
“…According to Loken et al (2009), approximately 70% of the expenses on feedlot production occur with the purchase of feeds, and approximately two-thirds of these expenses are associated with the concentrate feed. Among these feeds traditionally employed in animal production, corn stands out for the large volume utilized, and its use as whole grain has been an alternative for regions of low production of roughages, aiming at lowering the starch fermentation speed, in addition to reducing the costs related to the concentrate feed due to the lower degree of processing of this ingredient.…”
Section: Introductionmentioning
confidence: 99%